1987
DOI: 10.1212/wnl.37.3.439
|View full text |Cite
|
Sign up to set email alerts
|

Positron emission tomography and histopathology in Pick's disease

Abstract: PET using 18F-2-fluoro-2-deoxyglucose was carried out on a case of Pick's disease established by necropsy. A sharply decreased cortical metabolic rate for glucose was obtained in specific gyri, especially in the frontal lobes, where there was extensive gliosis and neuronal loss. More moderate decreases were found in areas with numerous Pick bodies and inflated neurons but less gliosis. The PET pattern was sufficiently distinctive to suggest that it might be possible to distinguish Pick's from Alzheimer's disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
4

Year Published

1987
1987
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(29 citation statements)
references
References 0 publications
4
21
0
4
Order By: Relevance
“…In addition, the present study suggests that dementia in CBD may be associated with degeneration in the iPF cortex. Our CBD patients exhibited hypoperfusion in the inferior and medial frontal regions which frequently are damaged in Pick's disease as well [22,23]. Thus, it looks likely that CBD and Pick's disease, at least in part, share the underlying mechanism of cognitive decline.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, the present study suggests that dementia in CBD may be associated with degeneration in the iPF cortex. Our CBD patients exhibited hypoperfusion in the inferior and medial frontal regions which frequently are damaged in Pick's disease as well [22,23]. Thus, it looks likely that CBD and Pick's disease, at least in part, share the underlying mechanism of cognitive decline.…”
Section: Discussionmentioning
confidence: 93%
“…Frontotemporal dementia is characterized by alterations in cerebral metabolism in the anterior cerebral regions, the metabolism in posterior association cortices being relatively preserved [29, 30, 31]. There is a notion of heterogeneity and subgroup formation in FTD, depending on the presence of language and speech disorders, motor abnormalities and the patterns of behavioral alterations.…”
Section: Discussionmentioning
confidence: 99%
“…This frontal hypoperfusion predicted the frontal pathology that characterizes FTD. Others confirmed these observations [17][18][19][20][21][22][23], and quantitative studies with positron emission tomography (PET) showed that patients with Pick's disease had diminished frontal lobe glucose uptake suggesting altered neuronal metabolism in the anterior brain regions [24][25][26][27][28]. Yet, despite these elegant clinical and imaging studies which should have allowed accurate diagnosis of FTD, the misdiagnosis rate for this condition has remained high [14].…”
Section: Historical Reviewmentioning
confidence: 97%